2019
DOI: 10.3390/su11030718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sycamore Maple Thermal Treatment on a Granulometric Composition of Chips Obtained due to Processing on a CNC Machining Mentre

Abstract: This article deals with a granulometric composition of chips from the milling process of native and thermal treatment maple cuttings on a 5-axial Computer numerical control (CNC) machining center SCM Tech Z5. The aim of this article was to determine the changes in the granulometric composition of chips due to the thermal treatment of wood and to assess the potential risk of the creation of harmful dust fractions. Cuttings were milled with a shank cutter with exchangeable razor blades at feed speed vf = 1 ÷ 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The feed rate reduction means the decrease of the nominal thickness of the particle and, thus, the particles move between finer fractions. This fact was also confirmed in the works [59,64]. The formation of dust particles can be from all open places of machines as well, especially on the premises of CNC machines as a result of maintenance, repairs, cleaning, inspection, tool change, etc.…”
Section: Resultssupporting
confidence: 58%
“…The feed rate reduction means the decrease of the nominal thickness of the particle and, thus, the particles move between finer fractions. This fact was also confirmed in the works [59,64]. The formation of dust particles can be from all open places of machines as well, especially on the premises of CNC machines as a result of maintenance, repairs, cleaning, inspection, tool change, etc.…”
Section: Resultssupporting
confidence: 58%
“…Dust fraction, (i.e., particles below 125 µm) was less than 1% in the case of native beech wood samples and less than 4% in thermally modified beech wood samples. When maple wood was thermally modified at a temperature of up to 137.5 ± 2.5 • C, significant changes in granular composition of particles resulting from the process of milling using a CNC (computer numerical control) milling center were not confirmed as it is mentioned by [60]. Similar results of particle granularity using the frame saw when modifying wood with lower temperatures were observed in the case of beech and pine wood [44].…”
Section: Thermal Modificationmentioning
confidence: 89%
“…However, in scientific publications on the dust generated during sanding thermally modified wood (oak, spruce, meranti), based on the sieve analysis performed, a lower content of particles with the smallest size was found in the dust from the wood modified at the highest temperature (220 °C) (Kučerka and Očkajová 2018;Očkajová et al 2019). The absence of the finest particles, that is less than 32 µm, was also found by Kminiak and Dzurenda (2019).…”
Section: Introductionmentioning
confidence: 56%
“…The analysis performed by Kminiak and Dzurenda (2019) showed that more than two thirds of the maple (Acer pseudoplatanus L.) wood particles produced during milling on a 5-axis CNC machining center were coarse-grained fractions, i.e., greater than 100 μm. The amount of particles with a size smaller than 125 μm did not exceed 2.5%.…”
Section: Introductionmentioning
confidence: 99%